A Critique of Economic Analysis of the ADA - Tolin, Tom; Patwell, Martin (Disability Studies Quarterly, 2003)
The purpose of this paper is to critique economic analysis of the Americans with Disabilities Act. Contrary to recent research, we conclude that the law did not create significant amounts of involuntary unemployment for workers with disabilities during the 1990s. Observed decreases in employment for this group can be explained, instead, as voluntary exits from the labor force. Our suggestions for more balanced economic analysis of the ADA conclude the paper.